Harnessing Biofilm-Mediated Plastic Biodegradation: Innovating Smart Material Design - Benes, Kaitlyn; Liguori, Madison; Velikaneye, Cody J.; Kispert, Sarah; Pishnyuk, Alexis; Luzik, Eddie; Sun, Hao; Xiao, Dequan; Gu, Huan (ACS applied engineering materials, 2025)
The persistent environmental challenges posed by synthetic plastics, particularly petroleum-derived petropolymers, such as polyethylene (PE), polypropylene (PP), and polystyrene (PS), have intensified the need for innovative recycling methods. Traditional recycling techniques often rely on harsh conditions, raising environmental and economic concerns. Biofilm-mediated biodegradation has emerged as a promising alternative, operating under mild conditions such as room temperature, neutral pH, and atmospheric pressure. However, the interactions between biofilm-forming microorganisms and synthetic plastics and the roles of secreted enzymes in these processes remain incompletely understood. This review explores the current understanding of biofilm-mediated biodegradationbiodeterioration, biofragmentation, bioassimilation, and mineralizationand the biochemical and physical interactions that control these processes. We highlight the latest findings on the enhancement of petropolymer degradation by biofilms, focusing on the roles of oxidative and attachment enzymes and the environmental factors influencing degradation efficiency. Understanding these complex interactions can inform the design of next-generation enzyme-responsive polymers that are not only easier to degrade but can also serve as smart materials for diverse applications, such as antifouling coatings on metals. This perspective bridges critical knowledge gaps and provides insights into harnessing biofilm-mediated processes for sustainable material innovation.